Peer Acceptance among Learning Disabilities (LD) and Mainstream Students in Inclusive Classroom in a Primary School - Mallanhanse, Armeetaa Kaur; Alias, Nur Fadzmin; Bidin, Siti Salma Najwa Bt Ahmad (South Asian Journal of Social Sciences and Humanities, 2020)
The need to include students with learning disabilities (LD) together with mainstream students in general education is vital in providing equal opportunity for all students regardless of their disabilities in obtaining the same education. Therefore, the present study aims in investigating peer acceptance from the perspectives of LD students and mainstream students, together with gender difference between these two group of learners in an inclusive classroom in a primary school in Sungai Petani, Kedah, Malaysia. The sample of this study consisted of 30 primary students involved in the inclusive programme within an age range of 8-11 years old. Data were collected using Acceptance Scale for Kindergarten-Revised. The findings revealed that there was no significant difference between LD and mainstream students on peer acceptance. Meanwhile, the analysis on gender differences revealed that there was a significant difference between male and female mainstream students on peer acceptance of their LD peers, in which male students reported higher peer acceptance than female students. While no gender differences were found among LD students on peer acceptance of their mainstream peers. The findings demonstrated that LD students are accepted in an inclusive classroom, indicating that mainstream students are willing to learn and experience education process together with LD students.